Aplikasi Foto Udara Dan Sistem Informasi Geografis Untuk Menilai Kemampuan Lahan Dan Tata Ruang Pertanian Jazirah Leihitu Kotamadya Ambon - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The study was carried out in Leihitu Peninsula, Ambon Municipality, with the objectives to study the accuracy and the ability of infrared black and white aerial photographs at scale of 1 : 10.000 in supporting the factors identification of land unit and agriculture land capability parameters in land capability, and space arrangement evaluation by mean of Geographical Information System. The method used was survey method by infrared black and white aerial photographic approach based on land unit and by overlaying landform map, slope map and land use map from aerial photographs interpretation. The factors of land unit was obtained completely from the aerial photographic interpretation. The land capability factors (slope, erosion level, and macro relief) were obtained from the aerial photographic interpretation, while the other factors (plant nutrient, plant-soil moisture, fertility holding capacity, permeability, erosion susceptibility, stoninness, salinity, ground water, dryness, soil depth, flood hazard and micro relief) can not be obtained from aerial photograph. They were acquired by field measurment. The land capability classes were measured by scoring method of land capability factors. Evaluation of agriculture space arrangement was done by overlaying land capability map and agriculture space arrangement map, using the ILWIS version 1.4 software. The result of this study indicated the interpretation accuracy either land capability factors or land unit factors were achieved for landform 88.0%, slope 89.4 %, landuse 93.5 %, erosion level 90.0 %, and macro relief 100 %. The result of land capability evaluation in the study area consisted of 5 classes, namely class II 746.6 ha (7.6 %), class III 6070.2 ha (62.0%), class IV 2712.8 ha (27.7%), class V 217.6 ha, (2.2 %), and class VI 37.8 ha (0.4 %). The result of evaluation of land arrangement for agriculture in the study area showed that space arrangement for agriculture was suitable as land capability classes, that the area for annual plants in class II was 156.6 ha (1.6%), class II/ 658.2 ha (6.7 %), and class IV 247.6 ha (2.5 %)